Surviving the economic crisis in distribution and warehousing business - Chai, Guan Sheng (2010)
Beginning with 20th century, globalization has promoted the free trade around the world. It is undeniable that globalization has boosted up the world economy. However, the interconnection of global common markets has highlighted an issue that an economy meltdown in any one given country could not be excluded as it would trigger a domino effect. Therefore, the financial excesses of subprime loans origins from the United States in year 2008 have turned into a full-scale global economic downturn, threatening the world trade through a credit crisis. In order to minimize losses from sales drop, manufacturers have to decrease productions following the significant fall in demand from consumer, the demand for storage and distributions decreased as the result of the impact. Consequently, distribution and warehousing businesses are hit by the large decline of international trades and GDP. However, not all distribution centers and warehouses are equally affected. Some are incurring huge losses on the verge of collapsing while others are surviving well. To regain an organization‟s profitability especially in distribution and warehousing business, companies may increase income or decrease the costs and expenses. Cost reduction and revenue enhancement will primarily be discussed in this report in order to examine varied strategies, in terms of feasibility and practicability. They are restructuring of work force, outsourcing, strategic alliances, mergers and acquisitions and diversification, and taking on value-added services. In conclusion, providing value-added services is a highly recommended strategy in order to achieve profitability and sustainability in the long run. Strategic alliances and outsourcing are more favorable to warehouses and distribution centers to achieve economic of scale and optimize the total supply chain value. Meanwhile, diversification, mergers and acquisitions, are not economically feasible during the downturn due to high capital requirement. Restructuring of work force is the last resort in an economic crisis as the negative impact of retrenchment is consequential to the company and society. Lastly, expansion and information technology development will be suggested to warehouses and distribution centers to sustain in the long run.